A modeling approach in the interpretation of starch pasting properties - Palabiyik, Ibrahim; Toker, Omer Said; Karaman, Safa; Yildiz, Onder (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2017)
In this work, starch pasting curves were reinterpreted with suitable models to show deficiency of widely used starch pasting parameters in the literature. The aim was to attract scientific attentions to the behavior and dynamics of the curve with respect to process parameters instead of values on the curve. Mainly, pasting curve was separated into four parts combining sigmoidal gelatinization model, exponential thinning model and Arrhenius temperature model. For the gelatinization part, starch swelling rate, water binding capacity and starch resistivities to heat and shear might be compared by the proposed model parameters. Amylose and damaged starch contents of starches had a good relation with Arrhenius and exponential model parameters. Activation energy values gave clues about retrogradation rate of starches and changed between 7142 and 17,327 kJ/mol. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Hill model; Starch; Viscosity; Pasting parameters; BRANCH CHAIN-LENGTH; PHYSICOCHEMICAL PROPERTIES; AMYLOSE CONTENT; GELATINIZATION; AMYLOPECTIN; SYNERESIS; GRANULES; GELS; Food Science & Technology